2021
DOI: 10.2807/1560-7917.es.2021.26.26.2100557
|View full text |Cite
|
Sign up to set email alerts
|

Neutralising capacity against Delta (B.1.617.2) and other variants of concern following Comirnaty (BNT162b2, BioNTech/Pfizer) vaccination in health care workers, Israel

Abstract: SARS-CoV-2 Delta (B.1.617.2) variant of concern (VOC) and other VOCs are spreading in Europe. Micro-neutralisation assays with sera obtained after Comirnaty (BNT162b2, BioNTech/Pfizer) vaccination in 36 healthcare workers (31 female) demonstrated significant fold change reduction in neutralising titres compared with the original virus: Gamma (P.1) 2.3, Beta (B.1.351) 10.4, Delta 2.1 and 2.6. The reduction of the Alpha (B.1.1.7) variant was not significant. Despite being lower, remaining neutralisation capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
109
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 17 publications
12
109
3
Order By: Relevance
“…The recent surge of cases in Israel 15 , one of the first countries to embark on a nationwide vaccination campaign (mostly with the BioNTech/Pfizer BNT162b2 vaccine), has raised concerns about vaccine effectiveness against the Delta variant, including official reports of decreased protection 16 . Concomitantly, studies have demonstrated only mild differences in short-term vaccine effectiveness 17 against the Delta variant, as well as substantial antibody response 18 . Apart from the variant, the new surge was also explained by the correlation found between time-from-vaccine and breakthrough infection rates, as early vaccinees were demonstrated to be significantly more at risk than late vaccinees 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The recent surge of cases in Israel 15 , one of the first countries to embark on a nationwide vaccination campaign (mostly with the BioNTech/Pfizer BNT162b2 vaccine), has raised concerns about vaccine effectiveness against the Delta variant, including official reports of decreased protection 16 . Concomitantly, studies have demonstrated only mild differences in short-term vaccine effectiveness 17 against the Delta variant, as well as substantial antibody response 18 . Apart from the variant, the new surge was also explained by the correlation found between time-from-vaccine and breakthrough infection rates, as early vaccinees were demonstrated to be significantly more at risk than late vaccinees 8 .…”
Section: Introductionmentioning
confidence: 99%
“…These vaccines have demonstrated high efficacy in clinical trials [15,16]. However, concerns remain regarding the rapid spread of new virus variants and the increasing number of new cases in countries with high percentages of vaccinated people [17][18][19][20]. We report six different cases of COVID-19 pneumonia in fully vaccinated patients.…”
Section: Introductionmentioning
confidence: 94%
“…However, numerous studies report markedly reduced neutralization of Beta by post-vaccination sera [4,11,12,[32][33][34], and some observational studies suggest moderately lower vaccine efficacy against Beta [24,31,35], although others show no reduction [36]. There is evidence suggesting slightly reduced neutralization of both Gamma and Delta by post-vaccination sera [15,18,19,34,37,38]; in the case of Delta, vaccine efficacy may be slightly reduced as well [20].…”
Section: Introductionmentioning
confidence: 99%
“…There is little evidence to suggest that Alpha evades vaccine-induced immunity; neutralization by post-vaccination sera is similar or slightly reduced compared to 12,28,29], and minimal differences in vaccine efficacy have been observed [23,30,31]. However, numerous studies report markedly reduced neutralization of Beta by post-vaccination sera [4,11,12,[32][33][34], and some observational studies suggest moderately lower vaccine efficacy against Beta [24,31,35], although others show no reduction [36]. There is evidence suggesting slightly reduced neutralization of both Gamma and Delta by post-vaccination sera [15,18,19,34,37,38]; in the case of Delta, vaccine efficacy may be slightly reduced as well [20].For individuals, the implications of variants with partial vaccine escape are straightforward: protection decreases linearly with the product of the variant's frequency in the population and the reduced efficacy against that variant.…”
mentioning
confidence: 99%